Morfología de la trompa de Eustaquio en cobayos (Cavia porcellus), gallo doméstico (Gallus gallus) y ranas (Rana catesbeiana) - Arch Tirado, Emilio; Verduzco Mendoza, Antonio; Leybón Ibarra, Jaime (Instituto de Ecología, A.C., 2006)
The aim of the present paper is to compare the morphology of Eustachian Tube (ET) in guinea pigs, domestic birds and frogs, with the purpose of analyzing the morphological differences among mammals, birds and batrachians. For the study 30 heads were used (10 for species) of the animals before mentioned. It was found that in these three species the TE is adapted to the habitat, in the case of the guinea pigs the torus tubarios is in the nasopharynx, in the birds is a torus tubarios (to bifurcate in toward the half hearing) in the roof of the oral cavity and in the frogs this in the lateral portion of the oropharynx and this permanently open one. The ET differs in size and it forms in the different species.